Un classique, une vedette. Les visages médiatiques de Gustave Flaubert (1880-1936) - Marie-Astrid Charlier (Flaubert: Revue Critique et Génétique)
This article proposes to draw the threads of Flaubert's media and symbolic edification through the faces of the man and the work that the press drew from his death in 1880 to the adaptation of Madame Bovary by Gaston Baty in 1936. Flaubert appears in turn as a master and a celebrity, according to a double process of classicisation and stardom of the author. The man who thundered against the tastes of the public has become, in spite of himself, a classic, even an untouchable in the history of French literature, while at the same time he has acquired post-mortem status as a star, who disliked - or rather declared himself to dislike - the press and public life in general.